Faktor-faktor yang Mempengaruhi Rupture Perineum pada Ibu Bersalin di Puskesmas Kecamatan Kramat Jati Jakarta Timur Periode Januari-Mei 2013 - Royani Chairiyah; Warsiningsih Warsiningsih (Jurnal Persada Husada Indonesia, 2015)
Rips the birth canal is the second leading cause after an atonic and often occurs in primiparous due tothe time of delivery do not get a strong grip, causing a tear in the perineum (South Bone, 2012). The dataDistrict Health Clinics Kramat Jati, East Jakarta, normal delivery in 2011 as many as 559 people found the caseof rupture of the perineum as many as 430 people (60%), while in 2012 as many as 538 people a normal deliverywith perineal rupture as much as 373 people (69%). The incidence of rupture of the perineum in PHC KramatJati, East Jakarta increasing the period of January to May 2013, 179 people with the amount of maternityperineal rupture 138 people (77%), rupture of the perineum grade I-II 87% and grade III-IV 13%. The purposeof this study to determine the factors that affect the incidence of maternal perineal rupture in Kramat JatiJakarta District Health Clinics east period from January to May 2013. This study uses an analytical methodpremises number of respondents 138 people. The results of the research that the frequency distribution ofrupture of the perineum by 138 people (77%), there was no significant association between maternal age on theincidence of rupture of the perineum, the value of P value is 0.692 or ≥ 0.05, there is a significant relationshipbetween the baby's weight on the incidence of rupture of the perineum , with the value of the P value is 0.000 or≤ 0.05, there is a significant relationship between the parity of the incidence of rupture of the perineum, thevalue of the P value is 0.033 or ≤ 0.05. From the results of research based on three variables in this study is thevariable weight infants 2500-4000 grams of the rupture of the perineum Grade I-II as many as 118 infants(93.7%). Suggestions for health centers are expected to increase efforts to prevent rupture of the perineum by providing counseling on maternal how meneran right to prevent rupture of the perineum and motivate pregnantwomen to pregnancy exercise and massage the perineum to reduce the incidence of rupture of the perineum.Keywords: Mother Maternity, Rupture Perineum